Voltammetric Study of a Cubic Silsesquioxane Organically Modified with Imidazole and their Subsequent Reaction with Cadmium and Hexacyanoferrate (III) - Silveira, Tayla Fernanda Serantoni da [UNESP]; Silvestrini, Daniela Rodrigues [UNESP]; Bicalho, Urquisa de Oliveira [UNESP]; Carmo, Devaney Ribeiro do [UNESP] (My University, 2013)
A hybrid nanocomposite formed by interaction of a octa (3-chloropropyl)octasilsesquioxane modified with imidazol , and its subsequent reaction with cadmium and hexacyanoferrate (II) (CdHSSI) was incorporated into a graphite paste electrode and the electrochemical studies were conducted with cyclic voltammetry. The cyclic voltammogram of the modified graphite paste electrode with CdHSSI (GPE- CdHSSI), showed one redox couple with formal potential Eθ=0.14V (vs Ag/AgCl, NaNO3, 1.0 mol L-1; v = 20 mV s-1), attributed to the Fe2+(CN)6/ Fe3+(CN)6 process. The redox couple presents an electrocatalytic response for determination of ascorbic acid. The modified electrode gives a linear range from 2.0×10-4 mol L-1 to 9.0×10-4 mol L-1 (r=0.998) for the determination of ascorbic acid with detection limit of 1.21×10-4 mol L-1 with a relative standard deviation of 5% (n=3) and amperometric sensitivity of 6.217 mA/ mol L-1 for ascorbic acid. © 2013 by ESG.
Keywords: Ascorbic acid; Graphite paste electrode; Imidazole; Silsesquioxane; Voltammetry